Introduction: Migrant Waves in the Making of America - Kathy G. Short (WOW Stories)
This issue of WOW Stories focuses on a literacy community that was created during a two-week NEH Summer Institute at Worlds of Words Center at the University of Arizona. The institute was attended by thirty K-12 teachers who came from across the U.S. to spend an intense two weeks together, meeting 9-4:30 in Worlds of Words Center in a range of explorations around migration.